A Review: Production Process Of Biodiesel Made From Wosten Oil Raw - Tanjung, Anggi Anggreini; Rahman, Susila Arita; Hadiah, Fitri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The development of biodiesel in Indonesia is increasing judging from consumption and export data to meet energy and fuel needs. The high cost of the biodiesel production process can be overcome by using waste cooking oil as a raw material. The use of waste cooking oil as biodiesel is an environmentally friendly action because it reduces environmental pollution. The method used in writing this article is a literature study by collecting data and information from various journals with the aim of explaining the processing of waste cooking oil into biodiesel. The catalysts used are acid and base catalysts (homogeneous, heterogeneous) and enzyme catalysts. Waste cooking oil can be converted into biodiesel by going through the transesterification stage. Under optimal conditions, used cooking oil as a raw material for biodiesel produces the highest methyl ester content of 98.94% using a heterogeneous base catalyst, namely ATKKS. The final conversion of biodiesel is affected by several parameters such as reaction temperature, reaction time, molar ratio of alcohol to oil, amount of fatty acids, moisture content and catalyst used.